Differential representations of spatial location by aperiodic and alpha oscillatory activity in working memory - Andrew Bender; Chong Zhao; Edward Vogel; Edward Awh; Bradley Voytek (Proceedings of the National Academy of Sciences, 2025)
Decades of research have shown working memory (WM) relies on sustained prefrontal cortical activity and visual extrastriate activity, particularly in the alpha (8 to 12 Hz) frequency range. This alpha activity tracks the spatial location of WM items, even when spatial position is task-irrelevant and no stimulus is currently being presented. Traditional analyses of putative oscillations using bandpass filters, however, conflate oscillations with nonoscillatory aperiodic activity. Here, we reanalyzed seven human electroencephalography visual WM datasets to test the hypothesis that aperiodic activity, which is thought to reflect the relative contributions of excitatory and inhibitory drive-plays a distinct role in visual WM from true alpha oscillations. To do this, we developed a time-resolved spectral parameterization approach to disentangle oscillations from aperiodic activity during WM encoding and maintenance. Across all seven tasks, totaling 112 participants, we captured the representation of spatial location from total alpha power using inverted encoding models (IEMs), replicating traditional analyses. We then trained separate IEMs to estimate the strength of spatial location representation from aperiodic-adjusted alpha (reflecting just the oscillatory component) and aperiodic activity and find that IEM performance improves for aperiodic-adjusted alpha compared to total alpha power that blends the two signals. We also identify a distinct role for aperiodic activity, where IEM performance trained on aperiodic activity is highest during stimulus presentation, but not during the WM maintenance period. Our results emphasize the importance of controlling for aperiodic activity when studying neural oscillations while uncovering a functional role for aperiodic activity in encoding visual WM information.